ANALISI PENGUASAAN KATA KETERANGAN "DAGAI" DAN "DAYUE" PADA MAHASISWA 2016 PRODI BAHASA MANDARIN UNTAN - Amalia, Kiki; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstractâ€œDagaiâ€ and â€œdayueâ€are types of adverbs that express possibilities that are often found in Mandarin, both of them are used to express predictions about something that is still predicted. Although these two words have almost the same meaning, but there are some differences between these two words, for example: differences in use, application to different scopes, and so on. These things cause mistakes for the student in using these two words. The author conducted research on the 2016 batch of Tanjungpura University to find out how the level of mastery and analysis difficulties of adverbs â€œdagaiâ€ and â€œdayueâ€. The author used the research test method to collect data. The results showed that when the students were studying these two words, they were good enough in using the adverb â€œdayueâ€, but for the use of the adverb â€œdagaiâ€ they still did not master it well. In analyzing the difficulties, the author analyzed it through the section on choosing the right placement. The author found that the mistakes that often occurred in learning these two words for the students is that they put these two words in the wrong position, resulting in grammatical errors.Â Keywords: Adverbs, dagai and dayue, Analysis of mastery